PENANGANAN PERILAKU BULLYING SISWA MELALUI KONSELING MODEL PENGEMBANGAN KOMITMEN BERAGAMA - Ulfiah Ulfiah (Psympathic : Jurnal Ilmiah Psikologi, 2008)
The glowing up bullying actor today certainly should be faced seriously by all side. School as one component in building students behavior is expected to set a sufficient medium that able to cut the bullying chain. Counseling program with the religious commitment development model is expected to deal with bullying behavior done by students in the school. This based on a number of studies suggest that the success of religious commitment development in dealing the difficulty behavior.